Isolation of bergenin from the root bark of Securinega virosa and evaluation of its potential sleep promoting effect - Mohammad Magaji; Aliyu Musa; Musa Abdullahi; Jamilu Ya'u; Isa Hussaini (Mashhad University of Medical Sciences, 2015)
Objectives: Securinega virosa Roxb (Ex Willd) Baill (Euphorbaiceae) root bark has been reportedly used in African traditional medicine in the management of mental illnesses. Previously, the sleep-inducing potential of the crude methanol root bark of Securinega virosa extract and its butanol fraction have been reported. The study aimed to isolate and characterize the bioactive constituent that may be responsible for the sleep inducing property of the root of the plant. Materials and Methods: The phytochemical investigation of the S. virosa root bark was carried out leading to the isolation of a compound from the butanol-soluble fraction of the methanol extract. The structure of the compound was elucidated on the basis of its spectral data, including IR, 1D and 2D NMR, mass spectrometry as well as X-ray diffraction analysis. The compound was investigated for sleep-inducing potential using diazepam-induced sleeping time test and beam walking assay in mice. Results: This is the first report on the isolation of bergenin from the root of the plant. It significantly decreased the mean onset of sleep [F (2, 15) =7.167; P < 0.01] at the dose of 10 mg/kg, without significantly affecting the total sleep duration [F (2, 15) = 0.090, P=0.914]. Conversely, it did not significantly affect the number of foot slips at the doses of 5 and 10 mg/kg tested. Conclusion: Bergenin isolated from the root bark of S. virosa possesses sleep-inducing property and could be partly responsible for the sedative potential of the root of S. virosa.